Resilient Organizations in Turbulent Economies: A Conceptual Model of Adaptive Strategy - Riinawati Riinawati (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study develops a conceptual model of adaptive strategy to explain how organizations build resilience in turbulent economic environments. Increasing global uncertainty—driven by economic volatility, technological disruption, and geopolitical instability—has challenged traditional strategic management approaches that rely on stability and predictability. Existing frameworks often treat resilience and strategy as separate constructs, limiting their explanatory power in dynamic contexts. This study addresses this gap by integrating resilience theory and adaptive strategy into a unified conceptual framework. Using a qualitative conceptual approach, this research synthesizes insights from strategic management, organizational theory, and complexity theory. The proposed model conceptualizes resilience as a dynamic capability that enables organizations to anticipate, absorb, and adapt to external shocks. Adaptive strategy is framed as an iterative process shaped by environmental uncertainty, organizational learning, and resource reconfiguration. The study identifies three core dimensions of organizational resilience: strategic flexibility, adaptive capacity, and institutional alignment. These dimensions interact to form a feedback-driven system that enhances organizational survival and long-term performance. The findings suggest that resilience is not a static attribute but a continuous process of strategic adaptation. This study contributes to the literature by offering an integrative framework that bridges resilience and strategy, providing a foundation for future empirical research. From a managerial perspective, the model highlights the importance of agility, learning, and institutional responsiveness in navigating turbulent economic environments.